Assessment of flavivirus RNA stability and infectivity in various water environments - Yuka Sano; Hawraa Al-Alawi; Misao Himeno; Ryuichi Majima; Kazumi Haga; Myo Thura Kyaw; Satoshi Taniguchi; Meng Ling Moi (Tropical Medicine and Health, 2025)
Abstract Introduction Flaviviruses such as dengue virus (DENV), Zika virus (ZIKV), Japanese encephalitis virus (JEV), and Yellow fever virus (YFV) are mosquito-borne RNA viruses causing major public health threats in major parts of the world. While DENV and ZIKV have been detected in urine samples, data on the presence and stability of flaviviruses in the water environment are limited. Methods In this study, we determined the stability and infectivity of flavivirus in different water environments by utilizing RT-qPCR and plaque assay to explore the feasibility of environmental detection and surveillance of flaviviruses. Results Viral RNA could be detected for up to 49-days, at 4 °C, 25 °C and 37 °C temperatures, and infectious particles could be detected for up to 7 days. While our findings showed that flaviviral RNA has higher stability and better detection rates at lower temperatures, the infectious capacity of flaviviruses was comparatively short at 7 days. Conclusions Our results indicate that flaviviruses retains limited infectivity in general water environments and highlight the feasibility of detection and surveillance in various epidemiologic and environmental settings.